Pengaruh Debt to Equity Ratio, Current Ratio, Return on Asset, Total Asset Turnover, dan Perubahan Arus Kas Operasi Terhadap Return Saham - Juanita Putri Aison; Rosita Suryaningsih (Ultima Accounting : Jurnal Ilmu Akuntansi, 2013)
The objective of this research is to examine the effect of Debt to Equity Ratio (DER), Current Ratio (CR), Return On Asset (ROA), Total Asset Turnover (TAT), and Cash Flow from Operating (CFO) both partially and simultaneously towards share return. The objects of this study are manufacturin companies which were listed in Bursa Efek Indonesia in the period 2010-2012. The samples are 18 companies based on purposive sampling. The data used in this study are secondary data such as share prices and financial statements. The results of this study are (1) Debt to Equity Ratio (DER) partially has significant effect towards share return (2) Current Ratio (CR) partially has no significant effect towards share return (3) Return On Asset (ROA) partially has significant effect towards share return (4) Total Asset Turnover (TAT) partially has no significant effect towards share return (5) Cash Flow from Operating (CFO) partially has no significant effect towards share return (6) Debt to Equity Ratio (DER), Current Ratio (CR), Return On Asset (ROA), Total Asset Turnover (TAT), and Cash Flow from Operating (CFO) simultaneously have a significant effect towards share return. Keywords: Debt to Equity Ratio (DER), Current Ratio (CR), Return On Asset (ROA), Total Asset Turnover (TAT), Cash Flow from Operating (CFO), share return